Wifi flaw affects nearly all devices. Issue 11 (November 2017) - Unknown
Abstract : A vulnerability has been found in the WPA2 protocol used to secure wifi sessions. Discovered by Mathy Vanhoef of imec-DistriNet, the 'key reinstallation attack' (Krack) affects all devices using WPA2, which until now was considered the most secure protocol for wifi.